Exiting venture capital investments: Lessons from Finland - Jyrki Ali-Yrkkö; Ari Hyytinen; Johanna Liukkonen (The Research Institute of the Finnish Economy (ETLA), 2001)
Because the exit stage may have several feedback effects on the earlier stages (i.e. fundraising and investing) in the venture capital process, the long-run development of the venture capital industry is dependent on the exit possibilities the financial system generates. In this study, we consider the mechanisms through which the financial system enhances the exit possibilities. We examine the Finnish experiences because the historical importance of banks, the volatile nature of the Finnish economy and the young age of the venture capital industry suggest that the co-development of “the market for exits” may be instrumental for the development of the Finnish venture capital industry. Our analysis of aggregate level data suggests that despite its favorable development during the 1990s, the Finnish financial system may provide less than optimal exit venues for the Finnish venture capitalists. This is because of the strong clustering of initial public offerings (IPOs) and the volatility and certain other documented characteristics of the Finnish stock market. The market for mergers and acquisitions (M&As) has been quite active in Finland by international standards and should in principle provide a steady flow of trade sale opportunities for the venture capitalists. However, the overall time trend of M&As may be decaying once the size of the economy is controlled for. The results of a survey we administered to the Finnish venture capitalists confirm the conclusions based on the aggregate data. By using the data collected in the survey, we also document that the young venture capital firms are systematically more worried about the impact of their reputation on their fundraising and that they have exited sooner than the old, established venture capitalists. The findings are consistent with the importance of feedback effects and in line with Gompers' (1996) results that indicate grandstanding by the entrant venture capitalists in the US. – – Mahdollisuudet irtautua tehdyistä sijoituksista kannattavasti vaikuttavat pääomasijoittajien halukkuuteen tehdä sijoituksia sekä heidän mahdollisuuksiinsa kerätä uutta pääomaa jatkossa. Tämän vuoksi pääomasijoitustoimialan pitkänaikavälin kehitys riippuu myös siitä, kuinka hyvin rahoitusjärjestelmä tuottaa irtautumismahdollisuuksia. Tutkimuksessa tarkastellaan suomalaista rahoitusjärjestelmää tästä näkökulmasta. Tutkimuksen tarkastelu osoittaa, että huolimatta vahvasta kehityksestä 1990- luvulla, kotimaiset rahoitusmarkkinat eivät välttämättä vastaa pääomasijoittajien irtautumistarpeisiin. Osasyynä tähän ovat mm. listautumismahdollisuuksien voimakas syklisyys, kotimaisten osakemarkkinoiden volatiilisuus sekä eräät muut kotimaisten markkinoiden ominaisuudet. Yrityskauppoja on Suomessa tehty aktiivisesti, mutta kehityssuunta näyttäisi olevan pikemminkin laskeva sen jälkeen talouden koon kasvun vaikutus niiden määrän on otettu huomioon. Pääomasijoittajille tekemämme kyselyn tulokset tukevat päätelmiämme. Ne myös osoittavat, että iältään nuoret pääomasijoitusyhtiöt ovat huolissaan heikosta tunnettuudestaan (maineestaan) ja sen vaikutuksesta varainhankintaansa ja että ne ovat myös irtautuneet sijoituksistaan keskimäärin nopeammin kuin jo pidempään alalla toimineet. Nämä tulokset ovat yhdenmukaisia Gompersin (1996) ”grandstanding” - hypoteesin ja hänen yhdysvaltalaisella aineistollaan saamiensa tulosten kanssa. – pääomasijoittaminen ; irtautuminen ; osakemarkkinat ; yrityskaupat
Keywords: 330; venture capital; exit; stock market; mergers and acquisitions; Risikokapital; Finnland; Marktaustritt